Operational framework to identify intervention points for supporting a tenure- and governance-enabling environment for community forest enterprises in Nepal - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Initial piloting was completed through application of the framework to assess 12 community forest enterprises in Nepal. Next steps are to implement it elsewhere to ascertain its usefulness in other regions.